A Measurement of India's Trade Intensity with SAARC Countries - Sharma, Haldhar (Journal of Commerce and Trade, 2013)
South Asian Association for Regional Cooperation (SAARC) was established to enhance political and economic relations within the region and outside the region. India’s complementary economic structure provides significant gains within the trade block. In this context, this paper attempts to examine existing status of India-SAARC trade, their mutual trade, and thereby measuring trade intensity between India and SAARC. The present study is focus on only the founder member countries of South Asian Association for Regional Cooperation. SAARC consist less developing countries except India, Pakistan and Bangladesh. Due to the small size of the economies economic activities are at their low level and there by trade volume is also low. On 7th December 1995 SAARC Preferential Trading Arrangement (SAPTA) was come into existence and World Trade Organisation (WTO) also established in the same year, therefore present study has been divided into two time periods that is before 1995 (1987 to 1995) and after 1995 (1996 to 2006). Study revealed that India’s mutual trade and trade intensities are increasing over the period of time, study explores that after the existence of SAARC Preferential Trading Arrangement (SAPTA) and establishment of World Trade Organisation, mutual trade and trade intensities of export and import are increasing and also more than the desired level.